The Influence of Team Game Tournament (TGT) Model on The Learning Outcomes of Grade 4 Students In Malaka Sari 01 Elementary School - Dea Ramadillah; Ika Yatri (Eduvest - Journal of Universal Studies, 2024)
This study explores the effect of the Team Game Tournament (TGT) learning model on the learning outcomes of Grade 4 students at Malaka Sari 01 Elementary School. The TGT model, as a cooperative learning strategy, engages students in collaborative and competitive group activities aimed at enhancing cognitive, affective, and psychomotor domains. The research employs a quasi-experimental design involving 60 students, divided into experimental and control groups. Data was collected through pre-tests and post-tests, with statistical analysis conducted using SPSS 25 to evaluate normality, homogeneity, and t-tests. The findings reveal a significant improvement in the learning outcomes of students exposed to the TGT model, with the experimental group demonstrating higher post-test scores compared to the control group. The study concludes that the TGT model fosters active participation, teamwork, and engagement, leading to improved academic performance and better comprehension of IPAS (Natural and Social Sciences) subjects. The results underscore the potential of TGT as an effective pedagogical tool to create enjoyable and meaningful learning experiences for elementary students.